Structural Characterisation of Malonyl Flavonols in Leek (Allium porrum L.) Using High‐performance Liquid Chromatography and Mass Spectrometry. Issue 3 (28th December 2013) - Donna, Leonardo Di; Mazzotti, Fabio; Taverna, Domenico; Napoli, Anna; Sindona, Giovanni
ABSTRACT Introduction Vegetables contain a variety of phytochemicals that have the ability to modify enzymatic and chemical reactions, and therefore may have a positive influence on human health. In particular kaempferol is known to possess anti‐carcinogenic activity. Objective The purpose of this work was to determine the structure of glycosylated kaempferol derivatives, acylated with malonic acid on the sugar portion. Methods A methanolic extract of the leaves of Allium porrum L. was submitted to fractionation procedures through semi‐preparative HPLC/UV–MS techniques. The collected fractions were evaluated by accurate tandem mass spectrometry experiments using an electrospray ionisation (ESI) quadrupole time‐of‐flight instrument. Isolated compounds were hydrolysed in order to obtain information on the ester moieties. Results The structures of five compounds not previously reported in leek were determined. The molecules are mono‐hexose, di‐hexose and coumaroyl, feruloyl and caffeoyl acylated di‐hexose derivatives of kaempferol. The common characteristic of the structures relies on the presence of the malonyl moiety on the primary alcoholic function of the sugar immediately linked to the aglycone. Accurate tandem MS experiments and basic hydrolysis treatments revealed a sequence of the acylated glycosidic moieties. Conclusion A set of secondary metabolites of the aerial part of Allium porrum L. (leek) was identified and characterised by ESI/MS2. Knowledge of the presence of these first‐reported compounds in leek could provide the means for fully understanding of the metabolism of this plant in relation to the biosynthesis of the phenolics. Copyright © 2013 John Wiley & Sons, Ltd.